A novel protein (p10) induced by 12-O-tetradecanoyl-phorbol-13-acetate (TPA) and other hyperplasiogenic tumor-promoting and non-promoting agents in murine epidermis - Schlatterer-Krauter, Kathrin; Hecker, Erich (Anticancer research, 1999)
Treatment of murine epidermis with the tumor promotor 12-O-tetradecanoylphorbol-13-acetate (TPA) shows characteristic and significant changes in protein expression analyzed by 2D PAGE, compared to that of acetone-treated mouse epidermis. Of the seven de novo expressed proteins in TPA treated murine epidermis, one is a 44 kDa protein (p44) located nearby actin, and six proteins are in the low-molecular range between 10-20 kDa (p10, pY, pCa, p1, p2 and p3). Interestingly, the incomplete promoting and inflammative hyperplasiogen 12-O-retinoylphorbol-13-acetate (RPA) and the non-promoting but inflammative and hyperplasiogenic calcium-ionophore A23187 induced the same pattern of proteins observed in the pidermis of mice treated with TPA, with minor quantitative differences. In all cases, p10 expression was quantitative the most abundant. Partial sequencing of this protein has led to the conclusion that it is a novel protein with no such sequences in the database comparisons using FASTA and TFASTA computer programs of Genetics Computer Group. The data presented here do not strictly support the functional role of de novo induced proteins to tumor promotion, but show a causal relationship to hyperplasiogenic potency of TPA, RPA and A23187.
Gesehen am 16.02.2021